Lighting Up Redox Propulsion with Luminol Electrogenerated Chemiluminescence. Issue 1 (8th July 2013) - Bouffier, Laurent; Zigah, Dodzi; Adam, Catherine; Sentic, Milica; Fattah, Zahra; Manojlovic, Dragan; Kuhn, Alexander; Sojic, Neso
<x xml:space="preserve">Abstract</x> Particle self‐tracking: A blue‐light‐emitting swimmer driven by bipolar electrochemistry is reported here for the first time. The approach involves the controlled motion of a conducting carbon bead through localized oxygen bubble generation, resulting from the oxidation of hydrogen peroxide. Simultaneous oxidation of luminol leads to the emission of light through electrogenerated chemiluminescence.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>